Studies on Schismatoglottideae (Araceae) of Borneo XXXXVIII – Galantharum, a new genus for the Hottarum Clade - Boyce, P.C; Wong, Sin Yeng (International Aroid Society, Inc., 2015)
Galantharum is described as a new genus of Tribe Schismatoglottideae, with a single novel species, Galantharum kishii. Preliminary molecular analyses place Galantharum basal of a clade composed of Fenestratarum, Bakoa, Hottarum, two clades containing species currently assigned to Aridarum, and a clade of species presently included in Piptospatha.